Science and technology diplomacy: a framework at the national level. Issue 2 (3rd July 2017) - Zolfagharzadeh, Mohammad Mahdi; Aslani, Alireza; Sadabadi, Ali Asghar; Sanaei, Mahdi; Lesan Toosi, Fahimeh; Hajari, Mahdi
Abstract : Purpose: Science and technology diplomacy (STD) is an emerging area in the field of public policy and technology management. The purpose of this study is to overview the concept of STD based on the two approaches "Science and Technology" and "Diplomacy" to explain its necessity for Non-Aligned Movement member countries. Design/methodology/approach: To design the work, principal domains and sub-domains of STD are identified based on the thematic analysis. By using MAXQDA software, the initial codes are analyzed and validated for the case study. Then, six areas and 29 sub-areas are identified based on the fuzzy Delphi and the framework is designed. Findings: STD is defined from six scopes, including political, economics, law and legal issues, social sciences, philosophy and science and technology. Each scope has its own mechanism that is discussed in the article. Originality/value: This work is one of the first in the literature of science and technology policy making.